Study of Living Standards of the Population in the Terms of Regions of the Republic of Uzbekistan - Usmonov Parviz Shavkatovich (International Journal on Economics, Finance and Sustainable Development, 2022)
In this thesis, theoretical aspects of the concept, quantitative and qualitative characteristics of the standard of living of the population are considered. The socio-economic characteristics of the standard of living in the regions of Uzbekistan are analyzed.